Modelling the potential distribution of Bemisia tabaci in Europe in light of the climate change scenario. Issue 10 (26th February 2014) - Gilioli, Gianni; Pasquali, Sara; Parisi, Simone; Winter, Stephan
Abstract BACKGROUND Bemisia tabaci is a serious pest of agricultural and horticultural crops in greenhouses and fields around the world. This paper deals with the distribution of the pest under field conditions. In Europe, the insect is currently found in coastal regions of Mediterranean countries where it is subject to quarantine regulations. To assess the risk presented by B. tabaci to Europe, the area of potential establishment of this insect, in light of the climate change scenario, was assessed by a temperature‐dependent physiologically based demographic model (PBDM). RESULTS The simulated potential distribution under current climate conditions has been successfully validated with the available field records of B. tabaci in Europe. Considering climate change scenarios of +1 and +2 °C, range expansion by B. tabaci is predicted, particularly in Spain, France, Italy, Greece and along the Adriatic coast of the Balkans. Nonetheless, even under the scenario of +2 °C, northern European countries are not likely to be at risk of B. tabaci establishment because of climatic limitations. CONCLUSION Model validation with field observations and evaluation of uncertainties associated with model parameter variability support the reliability of model results. The PBDM developed here can be applied to other organisms and offers significant advantages for assessing the potential distribution of invasive species. © 2014 Society of Chemical Industry